Homozygous damaging SOD2 variant causes lethal neonatal dilated cardiomyopathy. Issue 1 (7th September 2019) - Almomani, Rowida; Herkert, Johanna C; Posafalvi, Anna; Post, Jan G; Boven, Ludolf G; van der Zwaag, Paul A; Willems, Peter H G M; van Veen-Hof, Ingrid H; Verhagen, Judith M A; Wessels, Marja W; Nikkels, Peter G J; Wintjes, Liesbeth T; et al.
Abstract : Background: Idiopathic dilated cardiomyopathy (DCM) is recognised to be a heritable disorder, yet clinical genetic testing does not produce a diagnosis in >50% of paediatric patients. Identifying a genetic cause is crucial because this knowledge can affect management options, cardiac surveillance in relatives and reproductive decision-making. In this study, we sought to identify the underlying genetic defect in a patient born to consanguineous parents with rapidly progressive DCM that led to death in early infancy. Methods and results: Exome sequencing revealed a potentially pathogenic, homozygous missense variant, c.542G>T, p.(Gly181Val), in SOD2 . This gene encodes superoxide dismutase 2 (SOD2) or manganese-superoxide dismutase, a mitochondrial matrix protein that scavenges oxygen radicals produced by oxidation-reduction and electron transport reactions occurring in mitochondria via conversion of superoxide anion (O2 –· ) into H2 O2 . Measurement of hydroethidine oxidation showed a significant increase in O2 −· levels in the patient's skin fibroblasts, as compared with controls, and this was paralleled by reduced catalytic activity of SOD2 in patient fibroblasts and muscle. Lentiviral complementation experiments demonstrated that mitochondrial SOD2 activity could be completely restored on transduction with wild type SOD2. Conclusion: Our results provide evidence that defective SOD2 may lead to toxic increases in the levels of damaging oxygen radicals in the neonatal heart, which can result in rapidly developing heart failure and death. We propose SOD2 as a novel nuclear-encoded mitochondrial protein involved in severe human neonatal cardiomyopathy, thus expanding the wide range of genetic factors involved in paediatric cardiomyopathies.